World development indicators 2010. (World Bank e-Library. World Development Indicators., 2010)
Looking for accurate, up-to-date data on development issues? 'World Development Indicators' is the World Bank's premier annual compilation of data about development. This indispensable statistical reference allows you to consult over 800 indicators for more than 150 economies and 14 country groups in more than 90 tables. It provides a current overview of the most recent data available as well as important regional data and income group analysis in six thematic sections: World View, People, Environment, Economy, States and Markets, and Global Links. World Development Indicators 2010 presents